Penguatan Struktur Madrasah dalam Penerapan TQM: Tinjauan Teori Strukturasi Anthony Giddens - Muhamad Jamaludin; Faidhur Rohim; Sutrisno; Firdaus; Suwadi (Kelola: Jurnal Manajemen Pendidikan, 2025)
This study explores the implementation of Total Quality Management (TQM) in schools through the lens of Anthony Giddens' structuration theory. Field findings reveal that TQM is often applied in a bureaucratic and symbolic manner, with minimal involvement from school members and a lack of participatory reflection forums. Using the structuration framework, this study highlights that TQM structures are not fixed entities, but are formed and reproduced through the social practices of school actors. Inequities in rules and resource distribution weaken the agency of school members, while the absence of reflective spaces hinders conscious structural transformation. The analysis shows that strengthening school members as active agents is essential in building a dynamic and sustainable quality management structure. Therefore, it is recommended that schools develop collaborative structures, ensure equitable distribution of resources, establish open forums for collective reflection, and integrate TQM principles into daily practices. This study contributes theoretically to quality management approaches in educational institutions by emphasizing the reciprocal relationship between structure and agency.